الرسوم المتحركة كأداة تعليمية مبتكرة: تحليل تجريبي لتحسين مهارة الاستماع في المدرسة الإسلامية الثانوية بتانجيرانج الجنوبية - Fauzi, Muhamad Rizal; Edidarmo, Toto; Fudhaili, Achmad (Kalimatuna: Journal of Arabic Research, 2024)
This research is aimed at revealing the use of animation as an innovative learning medium to teach listening skills to grade X students of Madrasah Aliyah Al-Syuko. This study aims to measure the extent of the effectiveness of this media in improving listening skills and identify supporting and inhibiting factors in its use. The research method used is a mixed method that combines quantitative and qualitative approaches. This study involved two groups, namely the experimental and control groups, consisting of 35 students of class X. Quantitative data analysis was carried out through pretest and posttest tests, while qualitative data analysis used the Miles, Huberman, and Saldana models. The results showed that the use of animation significantly improved students' listening skills, with the average pretest score increasing from 53.88 to 76.94 in the posttest. The N-Gain test result of 0.5291 showed a moderate level of effectiveness. Statistical analysis also showed a statistically significant difference between the two groups (p<0.05).